Developmental potentiality of insulating lightweight concrete based on cork and calcareous sand. Issue 9 (2nd May 2016) - Ziregue, Ahmed; Khenfer, Mohamed Mouldi; Quéneudec-t'Kint, Michèle; Montrelay, Nicolas
Abstract: The objective of this work is to show the potential of construction materials development by valorizing industrial coproducts, mainly waste from the manufacture of cork panels used for the insulation of buildings and calcareous sand waste from quarries. Physico-mechanical and thermal characteristics were chosen as criteria to assess the feasibility of these types of materials. Results show the significant effect of cork aggregates on lightness and consequently in improving the thermal performance of the developed concrete. A decrease in the rate of the thermal conductivity is recorded up to 89% for a maximum cork dosage relative to the referential concrete. Otherwise, there is a decrease in mechanical strength depending on the content of cork aggregates.